The Views of Secondary School Teachers about Refugee Students - Gömleksiz, Mehmet Nuri; Aslan, Sibel (Mustafa ÖZMUSUL, 2018)
The aim of this study is to determine secondary school teachers’ views about the refugee students. In this direction, the secondary school teachers’ views about refugee students’ attention, and attitude toward  their subject,  refugee students’ readiness, attention, and attitude toward their lesson content, and the suitability of methods, techniques which they use in their class to the readiness of refugee students were determined. Moreover, their views about the suitability of their equipments and materials to readiness of refugee students; the suitability of assesment and evaluation instruments for refugee students; and their views, ideas to develop and enrich their lessons were determined. In this study, qualitative research design was used. The study group consisted of the secondary school teachers worked at a state school in Elazığ city center in 2017-2018 academic year, second term. Maximum variation sampling method was used in the study. In determination of school, whether there are refugee students or not at that school was considered. From each branch two teachers were selected and totally 22 secondary school teachers were included in the study. In determination of these teachers, the views of headmaster and deputies head of the secondary school were considered. Volunteer branch teachers participated to the study. A semi-structured interview form, which was designed by the researcher was used for data collection. Six semi- structured questions were asked to identify teachers’ views about refugee students. These questions were reviewed by a professor and two assistant professors. The clarity of questions were negotiated with three secondary school teachers. Study results revealed that secondary school teachers have some problems in instruction of refugee students because of several reasons. Several recommendations are offered based on the research findings.